Where are the wormy mice? A reexamination of hybrid parasitism in the European house mouse hybrid zone - Baird, Stuart J E; Ribas, Alexis; Macholán, Miloš; Albrecht, Tomáš; Piálek, Jaroslav; Goüy de Bellocq, Joëlle (Evolution; international journal of organic evolution, 2012)
Wormy mice in a hybrid zone have been interpreted as evidence of low hybrid fitness, such that parasites contribute to species separation. However, because of its natural heterogeneity, observations of parasite load must be numerous with good field area coverage. We sampled 689 mice from 107 localities across the Bavaria-Bohemia region of the European house mouse hybrid zone and calculated their hybrid indices using 1401 diagnostic single nucleotide polymorphisms (SNPs). We tested whether hybrids have greater or lesser diversity and load of parasite helminths than additive expectations, performing load analyses on the four most common taxa. We found hybrids have significantly reduced diversity and load of each of the commonest helminths; rarer helminths further support reduced load. Although within-locality comparisons have little power, randomization tests show the repeated pattern is unlikely to be due to local parasite heterogeneity, and simulations show a patch of low parasite diversity is unlikely to fall by chance just so in the field area, such that it produces the observed effects. Our data therefore contradict the idea that helminths reduce hybrid fitness through increased load. We discuss a vicariant Red Queen model that implies immune genes tracking parasites will escape Dobzhansky-Muller incompatibilities, generating hybrid variants untargeted by parasites.
Keywords: hybridizace genetická; Hybridization, Genetic; Animals; jednonukleotidový polymorfismus; biodiverzita; Female; zvířata; mužské pohlaví; parazitární zátěž; Male; Mice; Parasite Load; Polymorphism, Single Nucleotide; Helminths; cizopasní červi; ženské pohlaví; Biodiversity; myši